The clinical spectrum and prevalence of hereditary ophthalmopathology child population in 12 districts of the Rostov region - O. L. Kireeva; O. V. Chlebnikova; S. S. Amelina; G. I. Elchinova; R. A. Zinchenko; V. V. Kadsjyshev; E. K. Ginter (Oftalʹmologiâ, 2014)
Purpose: to study the diversity of the clinical spectrum and prevalence of hereditary ophthalmopathology child population in 12 districts of the Rostov region.Methods: We conducted an epidemiological study of hereditary ophthalmopathology population of the Rostov region. the popula- tion surveyed 12 districts of the region — 497460 people, including 97345 children (0-18 years). Regardless of age for the selection of patients used the original protocol of genetic-epidemiological studies, developed over 30 years ago, in Genetic Epidemiology Labora- tory Medical Genetic Research Center.Results: In the group of the child population identified 84 patients from 72 families. the most commonly diagnosed congenital cataract various forms (36.1%), congenital horizontal nystagmus (18.0%), monogenic defects eyes (15.6%), congenital ptosis (15.6%), hereditary retinal dystrophy (9, 6%). the overall prevalence of hereditary eye diseases among the adult population was 2.42±0.25, children 8.63±0.94 to 10,000 people.Conclusion: Conducting genetic epidemiology studies will improve eye health and medical genetic care.